Concept of a programmable fixture for 3-Axis CNC - Ahmed Azmi, Mohamed Dalol; Saleh, Tanveer (Deer Hill Publications, 2017)
CNC machine is the one of the major reasons for industrial advancement in recent decades for its ability of producing accurate parts. The most common CNC machines are of 3-axis and adopted widely in the industrial sector. However, for producing more complicated parts 5-axis CNC machines are required. Although the introduction of the 5-axis machine came after the 3-axis CNC machine has established itself and many manufacturers did not make the move toward the newer model and its high pricing compared to the 3-axis model did not help either. In this time the development of a fixture or a platform to help transfer the 3-axis to a 5-axis to some degree. This paper discusses the concept of a programmable fixture that gives 3-axis CNC machine the freedom to act in similar manner as the 5-axis. The paper describes the mechanism with some initial results of the testing. Result showed that the platform moves in translation manner with an average error of 5.58 % and 7.303% average error for rotation movement